Technological Innovation for Occupational Health: A Narrative Review of Workplace Risk Mitigation Strategies - Falaah, Fathi (Yayasan Sinergi Kawula Muda, 2023)
Occupational health remains a global priority, particularly for high risk sectors such as healthcare, where workers face complex and evolving hazards. This narrative review examines the challenges of workplace safety, with an emphasis on the transformative role of technological innovation during and beyond the COVID 19 pandemic. A systematic search across Scopus, PubMed, and Google Scholar identified key themes, including stress related disorders, exposure risks, and the effectiveness of various interventions. Findings indicate that insufficient public health infrastructure, lack of training, and limited mental health resources exacerbate occupational risks. Effective mitigation strategies include improved access to personal protective equipment (PPE), tailored psychological support, and advanced digital tools such as AI based risk assessments and wearable monitoring systems. These technologies offer promising avenues to enhance preventive measures and enable real time hazard management. The study underscores the urgent need for integrated policies, increased investment in occupational safety, and cross sectoral collaboration to ensure equitable protection. Future research should prioritize longitudinal analyses of health impacts, global comparisons of safety protocols, and expanded evaluation of emerging technologies. A multidisciplinary and proactive approach is vital for building safer and more resilient work environments.